(untitled) (Research, Society and Development, 2020)
The dentigerous cyst is an odontogenic cyst of development, it is exact cause is still unknown, but some theories have been proposed. This lession it is the second most common cyst of the jaw in the posterior sector at the level of the third molar and has a frequency of 20.6%, it is usually presents between 10 and 30 years of age with a predilection for the male sex. It is an asymptomatic lesion unless it presents infection, they are discovered by a radiographic finding and its treatment consists of enucleation and in some cases marsupialization. The objective of this article, which shows a case of a dentigerous cyst with its characteristics, lies in the importance of its conservative treatment for the subsequent mandibular bone regeneration and rehabilitation with dental implants in order to restore function and quality of life to an elderly patient, whose postoperative follow-up was 10 months.